2005
DOI: 10.1523/jneurosci.1227-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Brain Potential Correlates of Human Auditory Sensory Memory-Trace Formation

Abstract: The event-related potential (ERP) component mismatch negativity (MMN) is a neural marker of human echoic memory. MMN is elicited by deviant sounds embedded in a stream of frequent standards, reflecting the deviation from an inferred memory trace of the standard stimulus. The strength of this memory trace is thought to be proportional to the number of repetitions of the standard tone, visible as the progressive enhancement of MMN with number of repetitions (MMN memory-trace effect). However, no direct ERP corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
275
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(317 citation statements)
references
References 51 publications
31
275
11
Order By: Relevance
“…A Schmidt et al Consistent with other reports using a 'roving' oddball design (Baldeweg et al, 2004;Haenschel et al, 2005), an MMN memory trace effect was found in this study over the frontal cortex; however, no comparable effect was detected over temporal cortical regions. The absence of a temporal MMN memory trace effect suggests that the adaptation hypothesis (Jääskeläinen et al, 2004), which posits that the MMN results from local neuronal adaptation in the auditory cortex, cannot easily explain the MMN memory trace effect found in this study.…”
Section: S-ketamine-induced Cognitive Impairmentssupporting
confidence: 93%
See 2 more Smart Citations
“…A Schmidt et al Consistent with other reports using a 'roving' oddball design (Baldeweg et al, 2004;Haenschel et al, 2005), an MMN memory trace effect was found in this study over the frontal cortex; however, no comparable effect was detected over temporal cortical regions. The absence of a temporal MMN memory trace effect suggests that the adaptation hypothesis (Jääskeläinen et al, 2004), which posits that the MMN results from local neuronal adaptation in the auditory cortex, cannot easily explain the MMN memory trace effect found in this study.…”
Section: S-ketamine-induced Cognitive Impairmentssupporting
confidence: 93%
“…Electroencephalographic (EEG) activity was measured during an auditory 'roving' oddball paradigm (Baldeweg et al, 2004;Boly et al, 2011;Garrido et al, 2008;Haenschel et al, 2005), originally developed by Cowan et al (1993). Acoustic stimuli were generated by the E-prime software (Schneider et al, 2002), and applied binaurally through headphones (TDH-39-P; Maico, Minneapolis, MN).…”
Section: Auditory Test Paradigm (Mmn)mentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, this indicates that the component is to some extent modulated by target predictability, specifically by increments of surprise/prediction error. This effect needs further examination in 'attended' as well as 'unattended' settings with variations of stimulus onset asynchrony, rules, and the physical deviant/target features (Baldeweg, 2006;Haenschel, et al, 2005;Sussman, et al, 1998;Ulanovsky, et al, 2004). …”
Section: Area Of Applicationmentioning
confidence: 99%
“…Repetition effects are thought to reflect ongoing statistical learning during which the generative model is updated. In MMN studies RS often manifests as decrease of the negative component elicited by rare events, i.e., as a relative positivity to repeated stimuli, which was suggested to represent rapid SSA underlying sensory memory formation (Haenschel, Vernon, Dwivedi, Gruzelier, & Baldeweg, 2005). Predictive coding suggests that RS is brought about by fast changes in synaptic connections (Baldeweg, 2006(Baldeweg, , 2007Garrido et al, 2009) within and between hierarchical levels of neural populations.…”
mentioning
confidence: 99%